Capacity development workshop on Anticipatory Action - Alahacoon, Niranga; Amarnath, Giriraj; Gnanatheepan, W. (International Water Management Institute, 2023)
To enhance disaster management strategies in Sri Lanka, crucial change from reactive to proactive approach is important. Anticipatory Action, a proactive approach, involves early risk identification, monitoring, and preparedness measures. Establishing an Anticipatory Action framework requires collaboration and awareness among relevant agencies. A comprehensive two-day residence training program, designed by World Vision Lanka (WVL) and the International Water Management Institute (IWMI), aimed to equip government agencies with skills to develop Anticipatory Action protocols. The program covered key modules, including the concept of Anticipatory Action, components involving knowledge products and tools, distinctions from traditional response mechanisms, viability assessment, early warning practices, and the development of Anticipatory Action protocols and triggers. Special emphasis was placed on financial integration, MEAL planning, simulations, and addressing operational challenges. A total of 27 Participants from Disaster Management Centre (DMC), Department of Meteorology (DOM) National Building Research Organization (NBRO), Irrigation Department (ID), and National Disaster Relief Services Centre (NDRSC) actively participate for the training. The program utilized a module-based approach for an interactive learning experience. The program concluded with discussions on the way forward, emphasizing Anticipatory Action's essential role in national disaster reduction, highlighting a collaborative commitment to enhancing disaster preparedness and management in Sri Lanka.